Natural Sound Music Therapy On Sleep Disorders Of Post Operation Patients - Huda, Kholis Khoirul (Postgraduate Program , Poltekkes Kemenkes Semarang, 2022)
ABSTRAKSleep pattern disorders are disturbances in the quality and quantity of sleep due to external factors. In patients who have undergone surgery, sleep disturbances often occur, generally caused by pain (34.5%), fear of recurrent disease (17.24%), anxiety that it will not return to normal (10.3%), nurses' actions (10, 34%) and others (25%). Handling sleep pattern disorders using non-pharmacological therapy, one of which is natural sound music therapy. This study aims to determine the effect of natural sound music therapy on sleep disturbances in postoperative patients.The design of this research is Quasi Experiment with Posttest Only Control Group design. The sample of this study amounted to 12 people in the control group and 12 people in the intervention group. Statistical test results obtained p value = 0.000 (p value < = 0.05) there is an effect of natural sound music therapy on postoperative patient sleep disturbances. The results of the analysis of the value of OR = 91,000, meaning that respondents who were given natural sound music therapy had 91,000 times the opportunity to have better sleep quality than respondents who were not given natural sound music therapy. surgery at the General Hospital. A Yani Metro City.